Pengaruh Intervensi Edukasi Menyusui Terhadap Keberhasilan Pemberian ASI Eksklusif: Systematic Literatur Review - Monalisa; Nina Rahmawati; Lasmini; Lisa Trina Arlym (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Exclusive breastfeeding during the first six months of a baby's life plays an important role in optimal growth and development, but its coverage is still low in Indonesia. This study aims to review the effectiveness of breastfeeding education interventions on the success of exclusive breastfeeding through a Systematic Literature Review (SLR) using the PICOS framework. The search was conducted in the PubMed, ProQuest, SpringerLink, and ScienceDirect databases using the keywords “Breastfeeding Education” AND “Exclusive Breastfeeding” for English-language articles published between 2020 and 2025. Out of 260 articles found, 11 met the inclusion criteria and passed the quality assessment using the CEBM guidelines (score 8–12; Kappa=1.00). The analysis results showed that breastfeeding education, whether through conventional methods or digital technologies such as mHealth and chatbots, consistently improved self-efficacy, knowledge, and exclusive breastfeeding practices. Factors supporting the effectiveness of interventions include the role of healthcare workers, social support, and program integration into primary healthcare services. This review concludes that breastfeeding education has a significant positive impact on improving exclusive breastfeeding success and recommends its sustained implementation using a contextual approach that combines face-to-face and digital methods.